Motion Analysis and Biomechanics - Soutas-Little, R. W.
Classical, or Newtonian, mechanics is the oldest branch of physics devoted to the study of motion, the forces that cause that motion, and the internal forces that act within the body. Biomechanics is the application of Newtonian mechanics to the study of the neuromuscular skeletal system. Biomechanics has found its greatest use in orthopedics and physical medicine and rehabilitation characterizing function and dysfunction of the muscular skeletal system. One branch of biomechanics, gait analysis or motion analysis of human gait, has developed since early studies in the late 1900s. Motion analysis has been extended during the past two decades to investigate many other activities in addition to gait analysis. Currently, postural balance studies, stair ascending, or descending, and upper limbs are all being studied using motion analysis and the techniques of biodynamics. Although motion analysis requires the use of the mathematical techniques of dynamics, the presentation here will be on a conceptual basis where possible. TEMPORAL PARAMETERS OF THE GAIT CYCLE BODY SEGMENTS JOINT KINEMATICS GROUND REACTION FORCES KINETIC STUDIES POWER APPLICATIONS OF MOTION ANALYSIS AND BIOMECHANICS